Pregnancy and postpartum following a prenatal diagnosis of fetal thoracoabdominal malformation: the parental perspective. - Giuliani, Rosella; Tripani, Antonella; Pellizzoni, Sandra; Clarici, Andrea; Lonciari, Isabella; D'Ottavio, Giuseppina; Schleef, Jurgen (J Pediatr Surg, 2014)
PURPOSE: The study's aim was to evaluate how information related to a prenatal diagnosis of fetal malformation could modify parenthood experience descriptions during pregnancy and after the child's birth. METHODS: A longitudinal case-control clinical study was conducted. Data on parenthood experience descriptions collected using a validated semantic differential technique during pregnancy and after the child's birth were compared between seven couples of parents receiving a prenatal diagnosis of fetal malformation and seven couples without any fetal diagnosis. RESULTS: Our results show that during pregnancy parents in the clinical group describe themselves as more fragile, passive, and timid [p=0.007] than those in the control group. On the other hand, after the child's birth, there are no significant differences between groups. CONCLUSIONS: Data are discussed with reference to better knowledge of the psychological dynamics involved in becoming a parent and to rational planning of support for parents receiving a diagnosis of fetal malformation.
Keywords: Adult; Case-Control Studies; Counseling; Cystic Adenomatoid Malformation of Lung, Congenital; Female; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital; Humans; Hydronephrosis; Kidney Diseases; Longitudinal Studies; Male; Musculoskeletal Abnormalities; Parents; Pregnancy; Psychological Tests; Stress, Psychological; Ultrasonography, Prenatal; Urogenital Abnormalities

Third trimester abdominal circumference, estimated fetal weight and uterine artery doppler for the identification of newborns small and large for gestational age. - Di Lorenzo, Giovanni; Monasta, Lorenzo; Ceccarello, Matteo; Cecotti, Vera; D'Ottavio, Giuseppina (Eur J Obstet Gynecol Reprod Biol, 2013)
OBJECTIVE: To understand if ultrasound biometric evaluation at 30-32 weeks of gestation is a valuable screening tool for the detection of small-for-gestational-age (SGA) and large-for-gestational-age (LGA) infants at birth in a low risk population. STUDY DESIGN: We enrolled 1848 pregnant women with singleton pregnancy undergoing routine fetal biometry. We divided the infants into four groups: moderate SGA, severe SGA, moderate LGA and severe LGA. We considered third-trimester estimated fetal weight (EFW), abdominal circumference (AC), EFW centile (EFWc), AC centile (ACc) and compared their prediction toward SGA and LGA to determine which of these parameters was the best estimator for fetal size. Then we took the strongest predictive value and added all history-related and ultrasound factors to run a stepdown multivariate logistic regression. All the variables were then dichotomized and sensitivity models only for statistically significant parameters were calculated. RESULTS: We identified the following predictive factors for each outcome: for severe SGA: EFWc with p<0.001, uterine artery pulsatility index (UtA PI) with p<0.002. For moderate SGA: EFWc with p<0.001, UtA PI with p<0.004, maternal preeclampsia p<0.002. For moderate and severe LGA: EFWc with p<0.001. CONCLUSION: We can detect in a low-risk population a group at risk of growth deviations. Adding Doppler velocimetry to 30-32 weeks EFWc improves the specificity (84%) regarding SGA newborns, maintaining a good sensitivity (71%), and reducing the population to be re-screened from 27 to 17%. An ultrasound examination at 34-36 weeks or the clinical assessment of maternal risk factors remain the best tools for LGA newborns.
Keywords: Adult; Anthropometry; Birth Weight; Diabetes, Gestational; Female; Fetal Growth Retardation; Fetal Weight; Gestational Age; Humans; Hypertension, Pregnancy-Induced; Infant, Newborn; Infant, Small for Gestational Age; Pregnancy; Pregnancy Trimester, Third; Prospective Studies; Sensitivity and Specificity; Ultrasonography, Prenatal; Uterine Artery

Circulating TRAIL shows a significant post-partum decline associated to stressful conditions. - Zauli, Giorgio; Monasta, Lorenzo; Rimondi, Erika; Vecchi Brumatti, Liza; Radillo, Oriano; Ronfani, Luca; Montico, Marcella; D'Ottavio, Giuseppina; Alberico, Salvatore; Secchiero, Paola (PLoS One, 2011)
BACKGROUND: Since circulating levels of TNF-related apoptosis inducing ligand (TRAIL) may be important in the physiopathology of pregnancy, we tested the hypothesis that TRAIL levels change at delivery in response to stressful conditions. METHODS/PRINCIPAL FINDINGS: We conducted a longitudinal study in a cohort of 73 women examined at week 12, week 16, delivery and in the corresponding cord blood (CB). Serum TRAIL was assessed in relationship with maternal characteristics and to biochemical parameters. TRAIL did not vary between 12 (67.6±27.6 pg/ml, means±SD) and 16 (64.0±16.2 pg/ml) weeks' gestation, while displaying a significant decline after partum (49.3±26.4 pg/ml). Using a cut-off decline >20 pg/ml between week 12 and delivery, the subset of women with the higher decline of circulating TRAIL (41.7%) showed the following characteristics: i) nullipara, ii) higher age, iii) operational vaginal delivery or urgent CS, iv) did not receive analgesia during labor, v) induced labor. CB TRAIL was significantly higher (131.6±52 pg/ml) with respect to the corresponding maternal TRAIL, and the variables significantly associated with the first quartile of CB TRAIL (<90 pg/ml) were higher pre-pregnancy BMI, induction of labor and fetal distress. With respect to the biochemical parameters, maternal TRAIL at delivery showed an inverse correlation with C-reactive protein (CRP), total cortisol, glycemia and insulin at bivariate analysis, but only with CRP at multivariate analysis. CONCLUSIONS: Stressful partum conditions and elevated CRP levels are associated with a decrease of circulating TRAIL.
Keywords: Adult; Biological Markers; C-Reactive Protein; Female; Fetal Blood; Fetal Distress; Humans; Labor, Obstetric; Logistic Models; Multivariate Analysis; Postpartum Period; Pregnancy; Pregnancy Outcome; Statistics, Nonparametric; Stress, Physiological; TNF-Related Apoptosis-Inducing Ligand

Wired to be social: the ontogeny of human interaction. - Castiello, Umberto; Becchio, Cristina; Zoia, Stefania; Nelini, Cristian; Sartori, Luisa; Blason, Laura; D'Ottavio, Giuseppina; Bulgheroni, Maria; Gallese, Vittorio (PLoS One, 2010)
BACKGROUND: Newborns come into the world wired to socially interact. Is a propensity to socially oriented action already present before birth? Twin pregnancies provide a unique opportunity to investigate the social pre-wiring hypothesis. Although various types of inter-twins contact have been demonstrated starting from the 11(th) week of gestation, no study has so far investigated the critical question whether intra-pair contact is the result of motor planning rather then the accidental outcome of spatial proximity. METHODOLOGY/PRINCIPAL FINDINGS: Kinematic profiles of movements in five pairs of twin foetuses were studied by using four-dimensional ultrasonography during two separate recording sessions carried out at the 14(th) and 18(th) week of gestation. We demonstrate that by the 14th week of gestation twin foetuses do not only display movements directed towards the uterine wall and self-directed movements, but also movements specifically aimed at the co-twin, the proportion of which increases between the 14(th) and 18(th) gestational week. Kinematic analysis revealed that movement duration was longer and deceleration time was prolonged for other-directed movements compared to movements directed towards the uterine wall. Similar kinematic profiles were observed for movements directed towards the co-twin and self-directed movements aimed at the eye-region, i.e. the most delicate region of the body. CONCLUSIONS/SIGNIFICANCE: We conclude that performance of movements towards the co-twin is not accidental: already starting from the 14th week of gestation twin foetuses execute movements specifically aimed at the co-twin.
Keywords: Female; Fetus; Humans; Pregnancy; Social Behavior; Ultrasonography, Prenatal